(untitled) (Enki & Ptah. Journal of Technology and Trade in Ancient Egypt and Western Asia, 2025)
Review of Noemi Borrelli and Giulia Scazzosi (eds), After the Harvest. Storage Practices and Food Processing in Bronze Age Mesopotamia, Subartu XLIII, Brepols, Turnhout 2020, xii+146 p, 53 b/w, 14 tables b/w, Paperback - € 80,00, ISBN: 978-2-503-58378-5.